Regulation of FBP1 expression and changes in glucose metabolism are crucial for an appropriate response to DNA damage and aging in S.cerevisiae - Kitanovic, Ana (2006)
Exposure of living organisms to smaller amounts of toxic agents and other adverse effects may be more common in natural environments than direct impact of highly cytotoxic doses of the same agents. Occurring over various time spans or as the consequence of repeated exposures, the accumulation of mutations may be as critical for the organism as the immediate cytotoxic effect. Therefore, cellular response to the treatment with DNA-damaging substances at low concentrations which are genotoxic but do not have a strong cytotoxic effect are of special interest. Investigating the transcriptional response of S.cereveisiae to low doses of the alkylating agent methylmethane sulfonate (MMS) we observed that cellular sensitivity to MMS directly depends on their ability to immediately induce the basic, stereotypical stress response program called ESR. Modulation of basic metabolic pathways and induction of diauxic shift are factors that directly contributed to the increased resistance of the FF18984 strain to MMS. Metabolic adaptation and pre-induction of ESR resulting from nutrient deprivation helped this strain to cope better with the toxic effect of genotoxic agents applied later such as MMS. Our results showed that the major stimulus that triggers the adaptive response and the induction of ESR genes upon MMS treatment is an alteration in glucose utilization. These results point to an important correlation between metabolic pathways and the ability of living organisms to cope with adverse environmental conditions. Moreover, the induction of ESR seemed to be the most important prerequisite for a proper and fast cellular response to DNA damage. Expression of the key enzyme of gluconeogenesis fructose-1,6-bisphosphatase (FBP1) was clearly up-regulated by MMS in glucose-rich medium. Interestingly, deletion of FBP1 led to reduced sensitivity to MMS, but not to other DNA damaging agents such as 4-nitroquinoline (4-NQO) or phleomycin. The reduced sensitivity of the fbp1 mutant was the result of better recovery of this mutant after a long-term treatment with MMS. Reintroduction of FBP1 in the knockout strain restored the wild-type phenotype while overexpression increased MMS-sensitivity of wild-type. The connection between Fbp1p and one of the most important DNA damage signalling cascade that starts with the Mec1/Tel1 damage sensors was investigated with the RNR2-GFP reporter assay. These experiments revealed that the deletion of FBP1 had no effect on induction through the RNR2 promoter while overexpression of FBP1 significantly increased the activity of the RNR2 promoter. These results indicated that the increased intracellular level of Fbp1p after DNA damage caused by MMS probably acts as a signal that mediates cellular response to this toxic agent. Deletion of FBP1 reduced the production of reactive oxygen species (ROS) in response to MMS and in untreated aged cells. The mutant cells showed delayed production of ROS in the first fifteen days in aging culture what resulted in better viability in full medium. In minimal medium the lack of Fbp1p was no advantage for cellular survival. In these conditions aged fbp1 mutants survived even less and accumulated similar levels of ROS. Elevated amounts of Fbp1p shortened life-span, but did not have any influence on ROS accumulation. These results showed that Fbp1p is an important factor that modulates ROS production in response to MMS treatment and aging. However, in media with limited nutrients Fbp1p is a critical factor for cellular survival and its lack is rather a disadvantage. Based on the above observations, we concluded that FBP1 influences the connection between DNA damage, aging and oxidative stress either through direct signalling or an intricate adaptation in energy metabolism. In consequence, the tight regulation of FBP1 expression and age-associated changes in glucose metabolism are not only crucial for the control of gluconeogenesis but also for an appropriate response to aging and DNA damage.
Keywords: Hochschulschrift